1985
DOI: 10.2307/2987659
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Binomial Distribution

Abstract: This note sketches a biological context for the negative binomial distribution, gives some of the many equivalent mathematical notations that have been used for the negative binomial probabilities, and discusses the use of the computer program MLP (the Maximum Likelihood Program) for fitting negative binomial distributions to data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 16 publications
0
36
0
2
Order By: Relevance
“…In fact, in cases of under-dispersion, φ cannot be calculated directly (5,10). Second, the confidence intervals for α are also continuous and more symmetric than for φ .…”
Section: Probability Mass Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, in cases of under-dispersion, φ cannot be calculated directly (5,10). Second, the confidence intervals for α are also continuous and more symmetric than for φ .…”
Section: Probability Mass Functionmentioning
confidence: 98%
“…Second, the confidence intervals for α are also continuous and more symmetric than for φ . As the dataset becomes more homogeneous (φ ∞ ), the confidence intervals for φ can become erratic or discontinuous (10). For these reasons, it is recommended to estimate α directly.…”
Section: Probability Mass Functionmentioning
confidence: 99%
“…Hence, taking k 5 1 (Bernoulli distribution) we get a 5 À1 and S pop ðtÞ in (4) becomes S pop ðtÞ ¼ 1 À yFðtÞ, corresponding to the mixture cure model (Boag, 1949;Berkson and Gage, 1952). Ross and Preece (1985) showed that even if k 5 À1/a (ao0) is not an integer, the negative binomial distribution still furnishes positive values of P(N 5 m), m 5 0,1,y,k à , where k à is the largest integer less than k. From (3) it follows that the variance of the number of competing causes under the negative binomial model is flexible. If À1/yrao0, there is under-dispersion from the Poisson model.…”
Section: Modelmentioning
confidence: 99%
“…In fact, the range of models in Yin and Ibrahim (2005) is enlarged in our paper. Second, by adopting the so-called Fisher's parametrization for the negative binomial distribution (Ross and Preece, 1985), the likelihood function of our model includes the cured fraction. Furthermore, irrespective of the model, a unique expression relates the cured fraction to covariates.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, como não é intuito desta dissertação descrever o método da máxima verossimilhança para a estimação de parâmetros, são informadas as seguintes referências de (Crowley, 2012) e (Ross & Preece, 1985) De forma ratificar, que a função binomial negativa é a função que mais se aproxima da amostra analisada, mostra-se na tabela 7 os valores de logverossimilhança, AIC (Aikake Information Criterion) e BIC (Bayesian Information Criterion), ratificando que para função de log-verossimilhança quanto mais próximo de zero o número estiver mais próxima da amostra estará a distribuição estimada. Para os demais indicadores (i.e.…”
Section: Mge (Maximum Goodness Fit Estimation)unclassified